"Twisted Paths of Civilization": Saint Sara and the Romani - Petersen, Zina (Journal of religion and popular culture, 2014)
In conjunction with veneration for their onomastic patron saints, the Mediterranean town of Les-Saintes-Maries-de-la-Mer hosts a yearly festival for a unique saint, Sara. Her effigy housed in the church crypt, Sara is a draw for the Romani (aka "Gypsies") who venerate her and for the tourist industry, which relies on festival revenue. This article explores Sara's mythic and historic association with the Romani. It considers how racist thinking has infected Sara's story; it considers similarities between the Romani's ancestral Indian rites and today's Sara festivities. Finally, it suggests an indigenous Camarguaise tradition, pagan, then Christian, similar enough to Roma traditions to provide a framework for the Sara festival as it happens today. The festival may be as recent as the nineteenth century, but it is also as old as archetype.